224 PD-L1 Expression Reveals Significant Association With Squamous Differentiation in Upper Tract Urothelial Carcinoma. (11th January 2018) - Arriola, Aileen Grace; Jordan, Atasha; Chang, Joshua; Pearlman, Amy; Guzzo, Thomas; Lal, Priti
Abstract: Introduction: The immune checkpoint pathway is a promising target in cancer immunotherapy. Few studies have examined PD-L1 in upper tract (UT) urothelial carcinoma. In this study, we performed a comprehensive study of the differential expression of PD-L1 in UT tumors in relation to clinicopathologic features. Methods: 41 UT resections were identified, 14 with a history of bladder cancer (BC). Whole sections were stained for PD-L1, PD-1, and CD8. PD-L1 IHC was documented in epithelial and lymphohistiocytic compartments papillary cores (PC) and peritumoral (PT) in a semi-quantitative manner and H scores calculated (intensity X percentage). A cutoff of ≥1% membranous staining was considered positive. CD8 and PD-1+ lymphocytes were quantified. GraphPad was used for statistical analysis. Results: The frequency of UT PD-L1 expression in various tumor compartments was as follows: 39% epithelial, 25% PC, and 37% PT, with higher frequencies in pT3 tumors (10/15 epithelial; 4/15 PC; 9/15 PT). Twenty-five percent of UT tumors revealed >5% epithelial staining. By linear regression, epithelial PD-L1 expression was associated with squamous differentiation (SqD), tumor size, stage, and degree of tumoral lymphocytic (including PD-1+) infiltration (all P ≤ .05); and by multivariate regression, only SqD was significant ( P = .0002). Mean H scores for PD-L1 tended to be higher in tumors with SqD (mean 0.42, SD 0.6, n = 7/16) vs no-SqD (mean 0.09, SD 0.1, n = 9/16). CD8 and PD-1+ tumor infiltration was similar in the squamous vs non-squamous group. No difference in PD-L1 expression was noted in patients with UT only as compared to those with both UT and BC. Conclusions: In upper tract tumors, PD-L1 is strongly associated with squamous differentiation regardless of other clinicopathologic features. Tumors with squamous differentiation have higher PD-L1 H scores when compared to those without squamous differentiation. Larger studies are needed to further assess the significance of PD-L1 expression in upper tract urothelial carcinoma with squamous differentiation.